2020
DOI: 10.5755/j01.ms.26.4.23017
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Green Route to Silver Nanoparticles Using Aqueous Plant Extract, and their Photocatalytic and Antibacterial Studies

Abstract: Silver nanoparticles were prepared through an environmental friendly and cost-effective plant-mediated technique, using crude extracts of Welsh onion plant. The synthesized nanoparticles were characterized using UV-vis spectrophotometer, powdered X-ray diffractometer (p-XRD), Fourier transform infra-red (FTIR) spectrophotometer, and transmission electron microscope (TEM). Silver nanoparticles of different sizes and morphologies were obtained by varying some synthesis parameters such as concentrations of AgNO3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, green synthesis methods ensure the production of nanoparticles with welldefined shapes, sizes, and surface charges, enhancing their antimicrobial effectiveness [52]. Using natural reducing agents from plants or microorganisms can introduce additional antimicrobial compounds into the synthesis process, synergistically enhancing the overall antimicrobial activity of the nanoparticles [53]. A recent study reported varying inhibition zone diameters resulting from the antimicrobial activity of AgNPs against different bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, green synthesis methods ensure the production of nanoparticles with welldefined shapes, sizes, and surface charges, enhancing their antimicrobial effectiveness [52]. Using natural reducing agents from plants or microorganisms can introduce additional antimicrobial compounds into the synthesis process, synergistically enhancing the overall antimicrobial activity of the nanoparticles [53]. A recent study reported varying inhibition zone diameters resulting from the antimicrobial activity of AgNPs against different bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is essential to investigate plant extracts that include biomolecules that have inherent antibacterial activity in order to synthesize AgNPs with a rational antibacterial activity. [2,3,25,30,[47][48][49][50][51][52] A well-known hazardous element that has detrimental effects on both human health and the environment is mercury (Hg). Hg 2+ ions have been widely detected using a variety of sensing techniques, such as atomic absorption spectrometry (AAS), atomic emission spectrometry (AES), and inductively coupled plasma mass spectrometry (ICP-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to investigate plant extracts that include biomolecules that have inherent antibacterial activity in order to synthesize AgNPs with a rational antibacterial activity. [ 2 , 3 , 25 , 30 , 47 , 48 , 49 , 50 , 51 , 52 ]…”
Section: Introductionmentioning
confidence: 99%
“…Jun Xing et al 5 studied the active sites on hydrogen evolution photocatalyst and reported through a combined experimental approach, that metallic Pt nanoparticles have little contribution to the activity of photocatalytic H 2 evolution; the oxidized Pt species embedded on the TiO 2 surface are the key active sites and primarily responsible for the activity of the hydrogen evolution Pt/TiO 2 photocatalyst. DFT approach was also employed by Puente et al 12 , 13 in the scientific area of “Tailoring the interfacial interactions of van der Waals 1T-MoS 2 /C 60 Heterostructures for High-Performance Hydrogen Evolution Reaction Electrocatalysis and their result showed that the heterostructure domains of 1 T-MoS 2 and C 60 NSs exhibited excellent hydrogen evolution reaction (HER) performances, with one of the lowest onset potentials and ΔGH* values for LD non-precious nanomaterials. In furtherance, Lin et al, proposed alloying noble and non-noble metals as promising catalyst for HER.…”
Section: Introductionmentioning
confidence: 99%